The Influence Of The Role And Professionality Of Internal Audit On The Effectiveness Of Fixed Assets Internal Control At PT. AB - Fauziah Firda Widiastuti; Arni Karina (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to quantitatively assess the influence of internal audit professional and professional roles on the effectiveness of internal control of PTAB fixed assets based on saturated sampling methods. This study uses a sample of 42 respondents who work as internal auditors at PT. AB. The data of this study were analyzed using multiple regression analysis which is processed through IMB SPSS 23. The results show that the role and professional internal audit affect the internal control of fixed assets.